2013
DOI: 10.1021/jf302748z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capacity of Tomato Seed Oil in Solution and Its Redox Properties in Cultured Macrophages

Abstract: The health benefits of tomato seed oil (TSO) have been suggested to be related to its antioxidant activity, although at the moment not much information is available on the antioxidant effects of TSO in biological systems. In this paper, we evaluated the antioxidant capacity of TSO using different spectrophotometrical antioxidant assays (LPSC, FRAP, αTEAC, DPPH). Moreover, we determined the ability of TSO in inhibiting oxidative stress in human cultured macrophages. The peroxyl radical scavenging LPSC assay was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…1c). As a result, the β-carotene content in TSO was about 19.97 ± 1.80 mg/kg TSO which is comparable with the value reported by Müller et al [12]. Indeed, among the few studies interested in the content of carotenoids in TS and TSO, Müller et al [12] found that TSO contained 95.60 ± 3.60 mg lycopene/kg and 16.60 ± 0.40 mg β-carotene/kg TSO.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…1c). As a result, the β-carotene content in TSO was about 19.97 ± 1.80 mg/kg TSO which is comparable with the value reported by Müller et al [12]. Indeed, among the few studies interested in the content of carotenoids in TS and TSO, Müller et al [12] found that TSO contained 95.60 ± 3.60 mg lycopene/kg and 16.60 ± 0.40 mg β-carotene/kg TSO.…”
Section: Resultssupporting
confidence: 89%
“…Indeed, tomato peels were reported to contain, on dry basis, 14–20% protein [6, 7], 40–74% lignocellulosic material [68], and 3–5% oleoresin, being the oil fraction from tomato peels [9, 10]. Besides, tomato seeds were shown to contain 20–40% protein [11, 12], 35–50% lignocellulosic material [7, 13], and 18–37% oil [14, 15]. Nevertheless, currently, valorization of tomato peels has attracted little interest, since they are mostly considered for the extraction of carotenoids, especially lycopene [6], while tomato seeds have attracted very limited attention so far.…”
Section: Introductionmentioning
confidence: 99%
“…The unstable aldehydes had coupled without purification in a Wittig reaction with pentyltri-phenylphosphonium bromide to obtain (5Z,9Z,13Z)-octadeca-5,9,13-triene (6) in 88% yield (Fig. 5) [10,15].…”
Section: 3mentioning
confidence: 99%
“…A stirred solution of Trans, Cis, Cis-1,5,9-cyclododecatriene (2 gm, 12.3 mmol) in 50% (DCM/methanol) (100 mL) in a three-neck round bottom flask was fitted with three glass tubes to admit ozone, digital thermometer and condenser [10,15,17]. The flask was cooled down to (-62 °C to -48 °C) (liquid nitrogen/IMS).…”
Section: Preparation Of (4z8z)-1212-dimethoxydodeca-48-dien-1-olmentioning
confidence: 99%
See 1 more Smart Citation